Assessment of Bacterial Community Profile, Quality Impairment and Human Health Risk of Surface Water Receiving Abattoir Effluents: Evidence from Yewa and Iju Streams, Ondo State, Nigeria - , Ikuesan, Felix Adeleke, Loto, Olajide Olagoke, Ikuesan, Mobolaji Oluwole (Archives of Current Research International, 2025)
The discharge of untreated effluents into water bodies constitutes enormous threat to ecosystem sustainability and all forms of lives dependent on surface water resource. The purpose of this research was to assess the bacterial profile, quality impairment and human health risk of surface water receiving abattoir effluents. Water samples were collected from Yewa and Iju streams, Ondo State, Nigeria, both of which receives abattoir effluent. The microbiological and physicochemical analyses of the samples were carried out using conventional microbiological and physical and chemical analytical techniques. The samples showed significant number of heterotrophic bacteria of 4.6 x104 -2.1 x 106 CFU/mL and 1.8 x 104 -1.1 x 106 CFU/mL respectively for Yewa and Iju streams and coliform counts of 11-53 MPN/100 mL and 14-64 (MPN/100 mL. Four bacteria of the order Enterobacterales including Escherichia coli were isolated from the samples. The sampling points vary in their physicochemical parameters and concentration of heavy metals with pH in the range 6.58-7.27 and 6.74-8.65 for Yewa and Iju streams respectively. The biochemical oxygen demand for all the sampling points in both streams were above the 5 mg/L limit prescribed by the WHO. The water quality index of the streams was in the range 50.23-69.20 and 44.24-77.69 for Yewa and Iju streams respectively. A human health risk assessment of heavy metal exposure through dermal contact and ingestion revealed no significant hazard with hazard quotient (HQ) values of less than 1. In conclusion, the surface water receiving abattoir effluent can elicit substantial environmental and life-threatening public health concerns.